2020
DOI: 10.1016/j.ijom.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and adnexal anomalies in craniofacial microsomia: a systematic review

Abstract: Ocular anomalies may occur in craniofacial microsomia (CFM). The aim of this systematic review was to review the literature on ocular anomalies and their incidence, in order to estimate the need for ophthalmological screening in CFM patients. Online databases were searched, and data on the number of patients, type and incidence of ocular anomalies, and visual acuity were extracted. Four subgroups of ocular and adnexal anomalies were identified, to provide an overview of the different anomalies. Twenty-five pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
0
14
1
1
Order By: Relevance
“…The results of this study are mostly similar to the results of previous research regarding the prevalence of specific ocular anomalies. 14 However, the overall prevalence of ocular anomalies in this study is greater than the reported 17-24% in other relatively large patient cohorts 13,18,25,26 ; nevertheless, it should be noted that the aim of these previous studies was not always to report the prevalence of ocular anomalies. Furthermore, these studies did not report whether the patients underwent screening for ocular anomalies by an ophthalmologist.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…The results of this study are mostly similar to the results of previous research regarding the prevalence of specific ocular anomalies. 14 However, the overall prevalence of ocular anomalies in this study is greater than the reported 17-24% in other relatively large patient cohorts 13,18,25,26 ; nevertheless, it should be noted that the aim of these previous studies was not always to report the prevalence of ocular anomalies. Furthermore, these studies did not report whether the patients underwent screening for ocular anomalies by an ophthalmologist.…”
Section: Discussioncontrasting
confidence: 66%
“…This study is unique in that it describes ocular anomalies in the largest cohort of patients with CFM to date, thereby offering a detailed overview of the types and prevalence of ocular anomalies. Furthermore, this original study is novel in categorizing ocular anomalies using the classification proposed by our research group, 14 which offers a relatively concise separation of the anomalies and the impact they may have on the patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations